Al-Akhtha al-Shauthiyah fi Nuthq al-Lughah al-'Arabiyah li Fanan al-Mu'ashir: al-Atsar al-Mutartibah 'ala Ta'lim al-Lughah al-'Arabiyah - Fadli, Muhammad Fikri; Sari, Risna Rianti (Arabi : Journal of Arabic Studies, 2024)
This research aims to analyze phonetic errors in the recitation of Surah Al-Insyirah from the Qur'an by Rizky Billar and its implications for Arabic language education. Errors in makhraj (articulation points), characteristics of letters, nabr (stress), and tanghim (intonation) indicate challenges in learning Arabic phonology for non-Arab speakers. This research used a descriptive qualitative method with a content analysis approach on the YouTube video of Rizky Billar's recitation. Data were collected through observation, note-taking, and recording techniques, then analyzed based on the theories found in the Science of Al-Ashwat and Tajwid. The research results show that there are 12 types of phonological errors, including phoneme changes and meaning distortions due to incorrect pronunciation. These findings highlight the importance of phonetic-based pedagogical approaches, such as the talaqqi method, interactive phonology exercises, and the use of voice recognition technology in Arabic language learning. This research contributes to development of the Arabic language curriculum by emphasizing systematic phonological learning to enhance Quran reading skills and prevent fossilization in pronunciation errors.